SCHOOL PROMOTION AND POSITIONING EFFECTS ON SCHOOL CHOICE, MEDIATED BY BRAND EQUITY - Siti Nuraya Karo; Erwansyah (Fakultas Ekonomi Universitas IBA, 2025)
This study aims to examine and analyze the influence of school promotion and positioning on school choice decisions, with brand equity as a mediating variable at the Cendikia Bunayya Private Islamic Senior High School (MAS) in Kabanjahe, Karo Regency. Facing increasingly competitive educational institutions, promotional strategies and school image positioning are key to shaping public perception and attracting prospective students. Brand equity is positioned as a mediating variable that can strengthen the relationship between marketing strategy and school choice decisions. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 170 respondents, consisting of parents and students who had chosen MAS Cendikia Bunayya as their educational institution. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS). The results showed that school promotion and positioning had a positive and significant effect on school choice decisions. Furthermore, brand equity was shown to significantly mediate the relationship between promotion and positioning on school choice decisions. These findings underscore the importance of managing a school's marketing and branding strategies in building brand strength that can increase public interest in choosing that school.